Edukasi dan aksi kolaboratif mitigasi dampak perubahan iklim di Merauke - Adiatma, Tini; Yuliatun, Tutik; Novan, Muhammad; Majid, Ilham; Arafa, Guntur (Nur Science Institute, 2025)
Global climate change is a critical issue that demands collective attention and action from various sectors, including the academic community. This community service program aims to increase the awareness and involvement of the academic community, especially students and lecturers, in sustainable climate action. The activity was carried out collaboratively by Musamus University, WALHI, and the Sophia organization through three stages: guest lectures, Focus Group Discussions (FGDs), and the Ecology Academy. Guest lectures present speakers from environmental organizations who discuss climate change issues and their local relevance. FGDs explored community-based mitigation ideas, while the Ecology Academy provided training in developing practical and sustainable solutions. One hundred nineteen students from various study programs participated, with the level of understanding of the activity objectives reaching 95%. Although participation in the FGDs and the Academy was not maximized, this activity built awareness and initial commitment to environmental action. In the future, strengthening the participation mechanism and flexibility of implementation are expected to sustainably expand the program’s impact.